Nang Yai puppetry a dramatic art form of Thailand. - Meschke, Michael (SPAFA Journal : a publication of the SEAMEO Regional Centre for Archaelogy and Fine Arts)
Michael Meschke explores and documents an ancient theatrical art known as Nang Yai, which is a fusion of dance and puppet performance.